Effect of different levels of monensin with cold process urea molasses mineral block on rumen fermentation in vitro - DE, DEBASIS; SINGH, G P (The Indian Journal of Animal Sciences, 2014)
Rumen fluid was collected in 2 periods from rumen fistulated cattle adapted with moncnsin (50 mg/d) for 0 (period II) and 21 (period II) days for in vitro microbial fermentation study using wheat straw (WS) and concentrate mixture (3:2, T1), wheat straw and cold process urea molasses mineral block (UMMB) (6: 1; T2), in addition different level of monensin i.e., 35 ppm (T3), 70 ppm (T4), 100 ppm (T5), 150 ppm (T6) and 200 ppm (T7) as substrates. When rumen fluid was used from steer not adapted with monensin, the digestibility of DM, NDF, ADF, and total gas production was significantly lower in all monensin treatments (i.e. T3 T4 T5 T6 and T7) as compared to T1 and T2. Oil the other hand, when rumen liquor was used from monensin adapted steer the digestibility of DM, NDF, ADF, TVFA, and total gas production were not affected but propionate production significantly (P<0.05) increased and methane production significantly (P<0.0 1) decreased in all monensin treatments as compared to non-moncnsin treatments. But no significant difference in propionate proportion and methane production was observed among different levels of monensin treatments. So, it can be cond uded that after 21 days of adaptation with monensin fibre degrading ability of rumen microbes is not affected and 35 ppm level ofmonensin was sufficient to reduce methane production and resulted in an increase production of propionate.